BARAMULLA BECKONS: A HEAVEN FOR TRAVELERS IN JAMMU AND KASHMIR - Shabir Ahmad Lone; Nusrat-ul-Islam Itoo; R. Abida Begum; Mohammad Ishaq Lone (Universitas Efarina, 2024)
Tourism plays a pivotal role in fostering economic growth by generating revenue, creating employment, and contributing to GDP in many nations. Known for its unparalleled natural beauty, Kashmir is famously referred to as